Answer:
2 4 6
Step-by-step explanation:
Answer: ![\bold{\dfrac{4\pm \sqrt{6}}{2}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cdfrac%7B4%5Cpm%20%5Csqrt%7B6%7D%7D%7B2%7D%7D)
<u>Step-by-step explanation:</u>
![\dfrac{3}{y-2}-2=\dfrac{1}{y-1}\\\\\\\text{Multiply by the LCD (y-2)(y-1) to clear the denominator:}\\\\\dfrac{3}{y-2}(y-2)(y-1)-2(y-2)(y-1)=\dfrac{1}{y-1}(y-2)(y-1)\\\\\\3(y-1)-2(y-2)(y-1)=1(y-2)\\\\3y-3-2(y^2-3y+2)=y-2\\\\3y-3-2y^2+6y-4=y-2\\\\-2y^2+9y-7=y-2\\\\0=2y^2-8y+5\quad \rightarrow \quad a=2,\ b=-8,\ c=5\\\\\\\text{Quadratic formula is: }x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}\\\\\\x=\dfrac{-(-8)\pm \sqrt{(-8)^2-4(2)(5)}}{2(2)}\\\\\\.\ =\dfrac{8\pm \sqrt{64-40}}{2(2)}](https://tex.z-dn.net/?f=%5Cdfrac%7B3%7D%7By-2%7D-2%3D%5Cdfrac%7B1%7D%7By-1%7D%5C%5C%5C%5C%5C%5C%5Ctext%7BMultiply%20by%20the%20LCD%20%28y-2%29%28y-1%29%20to%20clear%20the%20denominator%3A%7D%5C%5C%5C%5C%5Cdfrac%7B3%7D%7By-2%7D%28y-2%29%28y-1%29-2%28y-2%29%28y-1%29%3D%5Cdfrac%7B1%7D%7By-1%7D%28y-2%29%28y-1%29%5C%5C%5C%5C%5C%5C3%28y-1%29-2%28y-2%29%28y-1%29%3D1%28y-2%29%5C%5C%5C%5C3y-3-2%28y%5E2-3y%2B2%29%3Dy-2%5C%5C%5C%5C3y-3-2y%5E2%2B6y-4%3Dy-2%5C%5C%5C%5C-2y%5E2%2B9y-7%3Dy-2%5C%5C%5C%5C0%3D2y%5E2-8y%2B5%5Cquad%20%5Crightarrow%20%5Cquad%20a%3D2%2C%5C%20b%3D-8%2C%5C%20c%3D5%5C%5C%5C%5C%5C%5C%5Ctext%7BQuadratic%20formula%20is%3A%20%7Dx%3D%5Cdfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%5C%5C%5C%5C%5C%5Cx%3D%5Cdfrac%7B-%28-8%29%5Cpm%20%5Csqrt%7B%28-8%29%5E2-4%282%29%285%29%7D%7D%7B2%282%29%7D%5C%5C%5C%5C%5C%5C.%5C%20%3D%5Cdfrac%7B8%5Cpm%20%5Csqrt%7B64-40%7D%7D%7B2%282%29%7D)
![.\ =\dfrac{8\pm \sqrt{24}}{2(2)}\\\\\\.\ =\dfrac{8\pm 2\sqrt{6}}{2(2)}\\\\\\.\ =\dfrac{4\pm \sqrt{6}}{2}](https://tex.z-dn.net/?f=.%5C%20%3D%5Cdfrac%7B8%5Cpm%20%5Csqrt%7B24%7D%7D%7B2%282%29%7D%5C%5C%5C%5C%5C%5C.%5C%20%3D%5Cdfrac%7B8%5Cpm%202%5Csqrt%7B6%7D%7D%7B2%282%29%7D%5C%5C%5C%5C%5C%5C.%5C%20%3D%5Cdfrac%7B4%5Cpm%20%5Csqrt%7B6%7D%7D%7B2%7D)
Answer:
270
Step-by-step explanation:
I am not sure if i am correct but i think you should divide 6,480 by 24 which is 270
Answer:
Option C.
Step-by-step explanation:
we know that
A relationship between two variables, x, and y, represent a direct variation if it can be expressed in the form
or
In a proportional relationship the constant of proportionality k is equal to the slope m of the line and the line passes through the origin
so
Find the value of the constant k
For the point (-8,-6)
![k=y/x=(-6/-8)=3/4](https://tex.z-dn.net/?f=k%3Dy%2Fx%3D%28-6%2F-8%29%3D3%2F4)
For the point (12,9)
![k=y/x=(9/12)=3/4](https://tex.z-dn.net/?f=k%3Dy%2Fx%3D%289%2F12%29%3D3%2F4)
<u><em>Note</em></u> A single point was required to find the constant k (because the line passes through the origin)
The equation is equal to